Conflict on Mount Lebanon : the Druze, the Maronites and collective memory - Rabah, Makram (Alternative histories., 2020)
"The Druze and the Maronites, arguably the two founding communities of modern Lebanon, have the reputation of being primordial enemies. Makram Rabah attempts to gauge the impact of collective memory on determining the course and the nature of the conflict between these communities in Mount Lebanon. He takes as his focus 'the War of the Mountain' in 1982, reconstructing the events of this war through the framework of collective remembrance and oral history."--